Parasitic bipolar effect in ultra-thin FD SOI MOSFETs. (October 2015) - Liu, F.Y.; Ionica, I.; Bawedin, M.; Cristoloveanu, S.
Abstract: The parasitic bipolar effect is investigated in fully-depleted silicon-on-insulator (FD SOI) n-type MOSFETs with ultra-thin films (5–10 nm). Our measurements show that at low drain bias the drain leakage current is governed by the gate current. Beyond VD > 1.0 V, leakage current amplification is observed in short-channel 10-nm thick devices. With film thickness shrinking, the current amplification is suppressed. We explain this amplification by the turn-on of the lateral parasitic bipolar transistor. TCAD simulations confirm that the parasitic bipolar is activated due to holes generated by band-to-band tunneling at the drain side and accumulated in the floating body. An effective method for the extraction of bipolar gain is proposed based on the comparison of leakage current in short- and long-channel devices. The experimental method is validated through simulations.